Systematic analysis of the interplay between synthesis route, microstructure, and thermoelectric performance in p-type Mg2Si0.2Sn0.8. (June 2019) - Kamila, H.; Goyal, G.K.; Sankhla, A.; Ponnusamy, P.; Mueller, E.; Dasgupta, T.; de Boor, J.
Abstract: For thermoelectric materials, the synthesis route is—besides composition—the crucial factor governing the thermoelectric transport properties and hence the performance of the material. Here, we present a systematic analysis of the influence of the synthesis technique on microstructure and thermoelectric transport properties in Li-doped Mg2 Si0.2 Sn0.8 . The samples were prepared using two wide-spread, but quite different synthesis methods: high energy ball milling and induction melting. Microstructural analysis (scanning electron microscopy and X-ray diffraction) reveals that ball milled samples are more homogenous than induction melted ones, which exhibit some Si-rich Mg2 (Si, Sn) and MgO as secondary phases. On a first glance, the thermoelectric properties are qualitatively similar with z T max ≈ 0.4 for both routes. However, a systematic analysis of the high temperature transport data in the framework of a single parabolic band model points out that the induction melted samples have a systematically reduced mobility and increased lattice thermal conductivity which can be tied to the differences in the microstructure. The reduced mobility can be attributed to a further carrier scattering mechanism for the induction melted samples in addition to the acoustic phonon and alloy scattering that are observed for both synthesis routes, while the increased lattice thermal conductivity is because of the larger grain size and presence of secondary phases. In consequence, this leads to significantly enhanced thermoelectric transport properties for ball milled samples (effective material parameter β is ∼ 20 % larger) and a predicted relative difference in device efficiency of more than 10%. Graphical abstract: Image 1 Highlights: Comparison of p-Mg2 Si0.2 Sn0.8 from ball milling (BM) and induction melting. Correlation of microstructure, synthesis route, and thermoelectric (TE) properties. Analysis of the TE properties using a SPB model reveals differences in the fundamental material parameters. Higher mobility and lower lattice thermal conductivity of the BM samples increase material quality factor and performance. Material-independent approach to identify a superior synthesis route.